Excessive Visit-to-Visit Small and Dense Low-Density Lipoproteins Elevate Cerebral Small Vessel Disease Progression Risk in the Elderly - Liu, Weike; Xu, Jing; Song, Huajing; Zhang, Chunju; Yao, Yanli; Zhang, Hua; Li, Yue-Chun; Liu, Zhendong (Frontiers in Neurology, 2022)
Objective: Small and dense low-density lipoprotein (sdLDL) elevation may be among the most sensitive early biomarkers for nascent cardiovascular disease. This study therefore investigated the association between visit-to-visit changes in sdLDL (sdLDL) and cerebral small vessel disease (CSVD) progression in older individuals, as well as the influence of Apolipoprotein E (APOE) genotype on this association. Methods: Between April 2007 and July 2009, 1143 participants ≥60 years old were recruited from the Shandong region of China, and sdLDL measured at baseline and at each follow-up visit. White matter hyperintensities (WMHs), lacunes, microbleeds, and enlarged perivascular spaces (EPVSs) were assessed by magnetic resonance imaging. The APOE genotype was determined and participants stratified as ε4-positive or ε4-negative. Results: During an average follow-up of 86.0 months, 225 participants (19.7%) developed WMH progression, 193 (16.9%) lacune progression, 170 (14.9%) microbleed progression, and 185 (16.2%) EPVS progression. Compared with patients in the first (lowest) tertile of visit-to-visit mean sdLDL, those in the second and third tertiles demonstrated significantly greater risks of WMH progression (53.5% and 105.3% higher), lacune progression (53.3% and 60.8%), microbleed progression (47.2% and 127.6%), and EPVS progression (54.0% and 135.0%) after adjustment for confounders (all adjusted P values for trends <0.001). Compared with patients in the first tertile of visit-to-visit sdLDL standard deviation (SD), those in the second and third tertiles also demonstrated significantly greater risks of WMH progression (49.9% and 143.6%), lacune progression (75.3% and 178.0%), microbleed progression (12.7% and 64.7%), and EPVS progression (41.7% and 114.6%) after adjustment (all P<0.001). There were significant and positive visit-to-visit mean sdLDL×visit-to-visit sdLDL SD, visit-to-visit mean sdLD×ε4-positive, visit-to-visit sdLDL SD×ε4-positive, and visit-to-visit mean sdLDL×visit-to-visit sdLDL SD×ε4-positive interactions influencing CSVD progression after confounder adjustment (all P<0.05). Conclusion: Large and variable visit-to-visit changes in sdLDL are independent predictors of aggressive CSVD progression, and this association is strongly influenced by APOE ε4 allele genotype.